PENGARUH KOMPETENSI, INDEPENDENSI, OBYEKTIVITAS, KECERMATAN PROFESIONAL DAN PENGALAMAN AUDIT TERHADAP KUALITAS AUDIT (Studi pada Pemeriksa Inspektorat Kabupaten/Kota di Aceh) - Nasriana, Hasan Basri, Syukriy Abdullah. (Universitas Syiah Kuala, 2015)
Abstract: Thisstudy is aimed to examine the effect of competence, independence, objectivity, due professional care, and audit experience on audit quality of examiners at the inspectorate districts/cities of Aceh either simultaneously or partially. The populations in this study are all the examiners at the inspectorate districts / cities in Aceh amount to 654 examiners with 98 samples taken. The data source of this research comes from the primary data obtain from the respondents through distributed questionnaire. Data analysis method use is multiple linear regression analysis. Results of the study show competence, independence, objectivity, due professional care and auditexperience simultaneously has a significant effect on audit quality of examiners at the inspectorate districts/cities of Aceh. The results also show that competence, objectivity and due professional care partially have a significant effect on audit quality of examiners at the inspectorate districts/cities of Aceh, whereas independence and audit experience have no significant effect on audit quality of examiners at the inspectorate districts/cities of Aceh. Keywords: Competence, Independence, Objectivity, Due Professional care, Audit Experience and Audit Quality Abstrak: Penelitian ini bertujuan untuk menguji pengaruh kompetensi,independensi, obyektivitas, kecermatan profesional, dan pengalaman audit terhadap kualitas audit pemeriksa inspektorat kabupaten/kota di Aceh baik secara simultan maupun parsial. Populasi dalam penelitian ini seluruh pemeriksa pada inspektorat kabupaten/kota di Aceh berjumlah 654 dengan jumlah sampel penelitian sebanyak 98 orang.Sumber data penelitian ini adalah data primer yaitu yangdiperoleh dari penyebaran kuisioner ke reponden penelitian. Metode analisi data yang digunakan adalah analisis regresi linear berganda. Hasil penelitian, menunjukkan kompetensi, independensi, obyektivitas, kecermatan profesional dan pengalaman audit secara simultan berpengaruh signifikan terhadap kualitas audit pemeriksa inspektorat kabupaten/kota di Aceh. Hasil penelitian secara parsial menunjukkan hanya kompetensi, obyektivitas dan kecermatan profesional yang berpengaruh signifikan terhadap kualitas audit pemeriksa inspektorat kabupaten/kota di Aceh sedangkan independensi, dan pengalaman audit tidak berpengaruh signifikan terhadap kualitas audit pemeriksa inspektorat kabupaten/kota di Aceh. Kata kunci : Kompetensi, Independensi, Obyektivitas, Kecermatan Profesional, Pengalaman Audit dan Kualitas Audit.